Auditoría de gestión aplicada al área de recursos humanos de la empresa el LLAVERO INTEGRAL S.A. - Jacome Burbano, Sandra Elizabeth (My University, 2019)
The audit for companies has been a fundamental activity for the rendering of accounts and has been applied in different ways to different areas, since not all the factors subjected to evaluation are the same. In the present investigation, the general objective was to determine recommendations through the preparation of an administrative audit report to optimize the management of the Human Resources area. The company under study is El Llavero Integral S.A. dedicated to making key rings with Smiley's; a descriptive methodology of five phases was used from the definition of the problem, information gathering, analysis of the problem and interpretation of the results, until the preparation of the audit report. Twelve work cards were prepared and statistical analyzes of the actual contribution of the subfunctions were made, which in the end allowed to know that there is less contribution from the activities aimed at the labor insertion and the development of the collaborators. The present investigation has allowed us to conclude that through the audit a better perspective of the real situation of the company has been reached and allowed to elaborate recommendations to focus on improving subfunctions with lower real value based on the findings.
La auditoría para las empresas ha venido siendo una actividad fundamental para la rendición de cuentas y se ha aplicado en distintas formas a distintas áreas, pues no todos los factores sometidos a evaluación son iguales. En la presente investigación se ha planteado como objetivo general determinar recomendaciones mediante la elaboración de un informe de auditoría administrativa para la optimización de la gestión del área de Recursos Humanos. La empresa objeto de estudio es El Llavero Integral S.A. dedicada a fabricar llaveros con Smiley’s; se utilizó una metodología descriptiva de cinco fases desde la definición de la problemática, levantamiento de información, análisis de la problemática e interpretación de los resultados, hasta la elaboración del informe de auditoría. Se realizaron doce cédulas de trabajo y elaboraron análisis estadísticos del aporte real de las subfunciones, que al final permitieron conocer que existe menor aporte de las actividades destinadas a la inserción laboral y al desarrollo de los colaboradores. La presente investigación ha permitido concluir que a través de la auditoría se ha alcanzado una mejor perspectiva de la situación real de la empresa y permitido elaborar recomendaciones para focalizarse en mejorar las subfunciones con menor valor real en función de los hallazgos.
Keywords: AUDITORÍA ADMINISTRATIVA; INFORME DE AUDITORÍA; CÉDULAS DE TRABAJO; RECURSOS HUMANOS